2003
DOI: 10.1017/s1355617703930037
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation related differences in spatial memory

Abstract: The purpose of this study was to investigate and extend previously reported sex differences in object location memory by comparing the performance of heterosexual and homosexual males and females. Subjects were 240 healthy, right-handed heterosexual and homosexual males and females. They were instructed to study 16 common, gender-neutral objects arranged randomly in an array and subsequently tested for object recall, object recognition and spatial location memory. Females recalled significantly more objects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 51 publications
5
23
1
Order By: Relevance
“…Our data support the notion that homosexual males may display cross-sex shifts in some aspects of spatial cognition (e.g. Gladue et al, 1990;Rahman and Wilson, 2003;Rahman et al, 2003b) but without the examination of search strategies this conclusion must be made cautiously. Similarly, without directly conducting translational studies of acquisition during spatial learning it is unclear to what extent our findings compare with previous animal work (e.g., Jonasson, 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data support the notion that homosexual males may display cross-sex shifts in some aspects of spatial cognition (e.g. Gladue et al, 1990;Rahman and Wilson, 2003;Rahman et al, 2003b) but without the examination of search strategies this conclusion must be made cautiously. Similarly, without directly conducting translational studies of acquisition during spatial learning it is unclear to what extent our findings compare with previous animal work (e.g., Jonasson, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Studies have consistently demonstrated that healthy adult heterosexual males out-perform homosexual males on male-favoring tests such as mental rotation, the water level test, and judgement of line orientation (Gladue et al, 1990;McCormick and Witelson, 1991;Wegesin, 1998;Neave et al, 1999;Rahman and Wilson, 2003). Homosexual males also performed better than heterosexual males in one study of a female-favoring spatial location memory test, suggesting some domain-specific dissociation of spatial processes (Rahman et al, 2003b). Moreover Rahman et al (2005) reported that homosexual males used a significantly greater landmark-based navigation strategy (female-favoring) than did heterosexual males.…”
Section: Introductionmentioning
confidence: 99%
“…20 Several independent studies consistently demonstrated low scores (female-typical) by homosexual men in basic spatial ability tests (such as mental rotation and spatial perception) compared with heterosexual men. 21 The possible reason for the absence of activation in the lingual gyrus of homosexual men is that they have a lower ability in spatial perception than heterosexual men.…”
Section: Discussionmentioning
confidence: 99%
“…For example, male homosexuals score closer to females in spatial cognitive tasks (Rahman, Wilson, & Abrahams, 2003;Wilson & Rahman, 2005), which may discourage homosexuals from sports involving hitting targets or engaging in complex spatial calculations where referential points are not close or in constant flux (like soccer). Considering that soccer and volleyball are team sports and both involve tracking and hitting objects as they move though space, soccer is more spatially complex than volleyball because the spatial orientation in a volleyball game is much more restricted using just few steps to achieve the ball; The main and the simple effects of the ANOVA 3 (sexual orientation) 92 (social class) 93 (nationality), controlling for age and consumer items are described as follows: * Significant differences were verified among the sexual orientations (p < .001; partial g 2 = .18), the social classes (p < .001; partial g 2 = .012) and the participants' nationality (p < .001; partial g 2 = .052) in the preference to play volleyball.…”
Section: Discussionmentioning
confidence: 99%